Addressing the threats of online theft of trade secret and cyber espionage in Malaysia: the legal landscape - Abd. Jalil, Juriah (Institute of Electrical and Electronics Engineers Inc., 2019)
Online theft of trade secrets and commercial cyber espionage are growing threats to businesses and national economy in this digital economy. This global phenomenon of targeting trade secrets of corporation has caused the loss of billions of dollars in the UK, US, Japan and some others. These crimes are committed by rivals and in most cases with the help of an insider who is normally an employee of the organization. In the US the prosecution of a Chinese national who disclosed a company trade secret in China while working in US indicated the cross border nature of the crimes. Responding to the threat, the US regards theft of trade secret and economic espionage in whatever form as crime against the state under the Economic Espionage Act 1996. In Japan such crimes are regarded as threats to the business industry that are penalized under the Unfair Competition Law of Japan. Although such decision broke the tradition of allowing mobility of workers and protecting the loyalty of workers in Japan, such law was introduced to protect the industry from unethical business practice and also to protect research and development to boost the Japanese economy. In contrast Malaysia like the UK has no specific law criminalizing economic espionage and theft of trade secrets even though the threats are growing. Without such laws the business community particularly the small business enterprises are exposed to this digital risks. However in relation to online theft of trade secrets and cyber espionage, the Communication and Multimedia Act 1998(CMA) and Computer Crimes Act 1997 (CCA) may be relied on to criminalized online theft of trade secrets and cyber espionage. By adopting SWOT and comparative analysis, this paper examines the administrative policy by the Malaysian Government and the current regulatory framework governing cyber espionage and online theft of trade secret in Malaysia. This paper concludes that both administrative policy and regulatory framework should complement each other to give better protection against online theft of trade secrets and commercial cyber espionage in Malaysia.